2017
DOI: 10.1016/j.jdent.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Translucent zirconia in the ceramic scenario for monolithic restorations: A flexural strength and translucency comparison test

Abstract: The zirconia composition heavily influenced both the flexural strength and the translucency. Different percentages of Yittria and Alumina result in new materials with intermediate properties in between the conventional zirconia and lithium disilicate. Clinical indications for Zirconia Aadva NT should be limited up to three-unit span bridges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
81
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 36 publications
12
81
0
8
Order By: Relevance
“…Furthermore, the substrate color affects the final esthetic outcome [29]. This is consistent with the findings of the previous studies, which have demonstrated that material type, thickness, and background color affect the shade of the final prosthesis [3,20,24,30]. Background color had a significant effect on the color of all the three selected materials at each thickness.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Furthermore, the substrate color affects the final esthetic outcome [29]. This is consistent with the findings of the previous studies, which have demonstrated that material type, thickness, and background color affect the shade of the final prosthesis [3,20,24,30]. Background color had a significant effect on the color of all the three selected materials at each thickness.…”
Section: Discussionsupporting
confidence: 88%
“…The high ΔE of Suprinity could be related to the incorporation of zirconia into its composition. Furthermore, the two types of crystals in its composition and inhomogeneity of the crystalline structure contribute to the high color difference values, which could result in low masking ability [3,20,30]. On the contrary, the high masking ability of lithium disilicate (IPS e.max) could be attributed to enhanced crystal structure and high translucency of a single type of crystal in its composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ceramic translucency is not high enough to imitate tooth structures, and consequently using this ceramic neighboring a natural tooth may compromise esthetics. Besides, the flexural strength of this ceramic is less than that of a framework zirconia (∼1200 MPa) or a high translucency monolithic zirconia (∼980 MPa), and therefore, this may increase the risk of fracture . Hence, the manufacturer contraindicates Katana Zirconia UTML for a fixed partial denture (3‐unit or longer), and also recommends a minimum thickness of 0.8 mm to compensate for the strength, but this may compromise the translucency …”
Section: Manufacturing Processesmentioning
confidence: 99%
“…Hence, monolithic ZrO 2 ceramics with 5 to 8% of yttria have emerged as having less opacity 60) . However, such a strategy sacrifices the flexural strength 66) and fracture toughness because of the partial loss of the transformation toughening effect of tetragonal ZrO 2 20,60) .…”
Section: Yttria Content (3% or 5-8%)mentioning
confidence: 99%